Case Report : Urolith Surgical Removal in a Green Iguana (Iguana iguana) (LAPORAN KASUS : BEDAH PENGELUARAN BATU KANTUNG KEMIH PADA SEEKOR IGUANA HIJAU (IGUANA IGUANA)) - Govendan, Puveanthan Nagappan; Ananthawijaya, I Gusti Made; Jayawarditha, Anak Agung Gede (Jurnal Veteriner, 2018)
Two years old male Green Iguana ( Iguana iguana ) weighing 1.3 kilograms presented with a swelling mass in the abdomen. Clinical signs, palpation and radiography images indicated urolith in the urinary bladder. The mass was radiopaque and had a width of 37 mm and a length of 41 mm. Clinical findings, examination and radio-imaging confirmed urolithiasis in the urinary bladder. Coeliotomy and cystotomy were performed to remove the urolith. Two days after surgery, the iguana regained its appetite and normal urate secretion was observed. Prognosis is good when surgery is performed on a healthy animal.